Developmental Experiences Related to Retirement from Sport: Insights from Japan. Issue 6 (18th August 2021) - Oulevey, Miyako; Hirata, Daisuke; Lavallee, David; Kohtake, Naohiko
Abstract: Psychological support systems for retiring elite athletes can assist them in making career transitions out of sport. The purpose of this study is to further advance research in this area, with a specific focus the developmental experiences related to the sport career transition process in Japan. One retired Olympic medalist was analyzed with a life story analysis method. The findings highlight the psychological difficulties experienced by retiring athletes and the system requirements to help them make an optimal transition.